Pengaruh Pemberian Permen Karet Xylitol terhadap Kesehatan Mulut (Xerostomia) pada Pasien Chronic Kidney Disease (CKD) - Peri Zuliani; Busjra M. Nur; Rohman Azzam (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
The purpose of this study was to determine whether there is an influence of xylitol gum administration in CKD patients. This type of research is a quantitative experiment with a pre post test design with a total sample of 20 respondents. Oral health of respondents was measured using the OHIP questionnaire with a Likert scale and scoring. The results showed there were differences in oral health before and after being given xylitol gum with a value of Ï value <0.05. Conclusion, administration of Xylitol gum affects the oral health (xerostomia) of CKD patients. Keywords: CKD, Oral Health (Xerostomia), Xylitol